A critique of the socio-cultural approach to development planning - Dirk Kohnert (Intereconomics, 1982)
Recent reflections on development policy have tried to eliminate the weak points in the economically oriented development theories which have dominated development planning up to now, and the traditional modernisation theories complementary to them. The propagation of strategies geared towards overcoming technological and cultural dependence is one result of such rethinking. The following article takes Black Africa as its case example for a critical appraisal of this “socio-cultural” approach – – Neuere entwicklungspolitische Überlegungen haben versucht, die Schwachstellen der ökonomisch orientierten Entwicklungstheorien, die die Entwicklungsplanung bisher dominierten, und der sie ergänzenden traditionellen Modernisierungstheorien zu beheben. Die Verbreitung von Strategien zur Überwindung technologischer und kultureller Abhängigkeiten ist ein Ergebnis dieses Umdenkens. Der folgende Artikel widmet sich am Beispiel des Sub-Sahara Afrikas einer kritischen Würdigung dieses ,,soziokulturellen“ Ansatzes.
Additional information: Author's revised version of: Kohnert, Dirk (1982): A critique of the socio-cultural approach to development planning, Intereconomics, Vol. 17 (6), Verlag Weltarchiv, Hamburg, pp. 296-301. https://doi.org/10.1007/BF02930175
Keywords: F35; F52; F54; H43; H84; N17; O15; O17; O22; Z13; 330; Entwicklungsplanung; Afrika südlich der Sahara; Modernisierungstheorien; Technologietransfer; Zielgruppenanalyse; pro-poor growth; Entwicklungshilfe; ODA